Prognostic impact of the choice of chemotherapy after first-line CDK4/6 inhibitor therapy in patients with metastatic hormone receptor-positive, HER2-negative breast cancer - Michel, Laura L.; Wallwiener, Markus; Schneeweiss, Andreas (European journal of cancer, 2025)
Introduction: Whereas CDK4/6 inhibitors (CDK4/6i) are the standard first-line therapy for patients with hormone receptor-positive (HRpos), HER2-negative (HER2neg) metastatic breast cancer, guidelines on treatment options after progression on CDK4/6i are more diverse. Chemotherapy is recommended if a patient develops endocrine resistance or experiences a visceral crisis. However, the impact of the choice of chemotherapy remains unknown. Methods: HRpos/HER2neg patients who received first-line CDK4/6i, followed by second-line chemotherapy (N=215) were selected from the prospective PRAEGNANT registry (NCT02338167). Cox regression analyses were used to evaluate the correlation between the choice of chemotherapy (capecitabine monotherapy, capecitabine + bevacizumab, taxane monotherapy, taxane + bevacizumab, anthracycline, other chemotherapeutics) and progression-free survival (PFS) and overall survival (OS). Results: Patients who received second-line chemotherapy mostly had high-grade tumors (G2: 62.3%, G3: 33.3%), visceral metastases (62.3%) and developed metastatic disease following a primary breast cancer diagnosis (73.8%). Capecitabine was the most common regimen (25.1%), followed by taxane +bevacizumab (17.2%). When adjusting for other prognostic factors (age, BMI, grading, ECOG, metastasis group and time to metastases), the choice of chemotherapy did not influence PFS (p=0.16) nor OS (p=0.47). Adjusted hazard ratios for PFS were lowest in regimens with bevacizumab (capecitabine as reference; capecitabine + bevacizumab: 0.53 (95%CI: 0.29, 0.97); taxane +bevacizumab: 0.64 (95%CI 0.35, 1.15)). Conclusion: Although the choice of chemotherapy post-CDK4/6i did not significantly affect PFS or OS, combinations with bevacizumab may have some benefit. Nevertheless, considering side effects may be most important when choosing the type of second-line chemotherapy.